ROLE OF MEAN PLATELET VOLUME IN THROMBOTIC STROKE - Ikra, Vandy (Majority, 2015)
Abstract Background: Stroke is a disease caused by many risk factors, it cause disability and death in developing countries and emerging. Thrombosis is a major complication of atherosclerosis process involving platelet activation and aggregation of ulcerated plaques that develop atherom. Atherotrombosis trigger local occlusion and embolism in the distal region with the clinical manifestations can be seen in ischemic stroke. Previous studies have described the association of MPV with heart disease, especially coronary heart disease, it is known that platelet activation and aggregation play a role in thrombus formation. Discussion: The pathogenesis of ischemic stroke begins from the formation of thrombus in both the walls of blood vessels and the heart. Thrombus formation in blood vessels initiated by damage to blood vessels. Increased MPV is thought to have a higher thrombotic effect than smaller platelet volume. Conclusion: MPV have an influence on the function and reactivity of platelets even MPV values ​​can be predictors of mortality associated with vascular disease (stroke and heart). Keywords: MPV, stroke, thrombosis, thrombotic stroke, Abstrak Latar belakang: Stroke adalah penyakit yang disebabkan oleh banyak faktor resiko, dan merupakan penyebab kecacatan serta kematian di negara-negara berkembang maupun yang sedang berkembang. Trombosis merupakan komplikasi utama dari proses aterosklerosis yang melibatkan aktivasi dan agregasi platelet yang berkembang dari ulserasi plak atherom. Atherotrombosis memicu terjadinya oklusi lokal dan embolisme di daerah distal. Dengan manifestasi klinis yang dapat dilihat pada stroke iskemik. Penelitian-penelitian sebelumnya telah menjelaskan hubungan MPV dengan penyakit jantung terutama jantung koroner, telah diketahui bahwa aktivasi dan agregrasi platelet berperan dalam pembentukan trombus. Pembahasan: Patogenesis stroke iskemik diawali dari dibentuknya trombus baik di dinding pembuluh darah maupun jantung. Terbentuknya trombus di pembuluh darah diawali oleh kerusakan di pembuluh darah. MPV diduga mempunyai efek trombotik yang lebih tinggi dibandingkan platelet yang volumenya lebih kecil. Kesimpulan: Nilai MPV mempunyai pengaruh dalam fungsi dan reaktivitas dari trombosit bahkan nilai MPV bisa dijadikan prediktor mortalitas yang berkaitan dengan penyakit vaskular (Stroke dan Jantung). Kata kunci: MPV, stroke, stroke trombotik, trombosis